ARKEOLOGI DAN PENGENALAN PRASEJARAH PERAHU NUSANTARA - Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2006)
The data which we found on maritime archaeology resulted several information The benefit of the result of maritime archaeology and the history sources would be done by identifying the prehistory of archipelago boat. It was regarding the benefit of: a. tied-up technique b. the combination of tied-up and peg technique, c. peg technique and other techniques which is used in boat production as a water transportation. In addition to the grouping of the technology of boat production, it could be known an chronological aspect.